Molecular Processes Involved in Pancreatic Cancer and Therapeutics - Makar, Subhajit; Ghosh, Abhrajyoti; Divya; Shivhare, Shalini; Kumar, Ashok; Singh, Sushil K. (Current Chemical Biology, 2021)
Despite advances in the development of cytotoxic and targeted therapies, pancreatic adenocarcinoma (PAC) remains a significant cause of cancer mortality worldwide. It is also difficult to detect it at an early stage due to a number of factors. Most of the patients are present with locally advanced or metastatic disease, which precludes curative resection. In the absence of effective screening methods, considerable efforts have been made to identify better systemic treatments during the past decade. This review describes the recent advances in molecular mechanisms involved in pancreatic cancer initiation, progression, and metastasis. Additionally, the importance of deregulated cellular signaling pathways and various cellular proteins as potential targets for developing novel therapeutic strategies against incurable forms of pancreatic cancer is reported. The emphasis is on the critical functions associated with growth factors and their receptors viz. c-MET/HGF, CTHRC1, TGF-β, JAK-STAT, cyclooxygenase pathway, WNT, CCK, MAPK-RAS-RAF, PI3K-AKT, Notch, src, IGF-1R, CDK2NA and chromatin regulation for the sustained growth, survival, and metastasis of pancreatic cancer cells. It also includes various therapeutic strategies viz. immunotherapy, surgical therapy, radiation therapy and chemotherapy.
Keywords: Notch